Późnośredniowieczne wsie w świetle badań archeologicznych - Marciniak-Kajzer, Anna (Zeszyty Wiejskie, 2016)
In this article the author presents some research on medieval rural settlements. However, they haven’t been the subject of systematic archaeological research in Poland yet. The most of them were rescue excavation on the sites discovered during sample researches conducted before the construction of motorways or building investments. Some of archeological sites were identified during the Polish Archaeological Record survey (AZP) and they were mapped. The practical approaches of major archaeological investigations towards medieval settlement have included aerial photography that allowed to record many sites. Presented archaeological site was discovered on air photograph showing the characteristic vegetation dissimilarities. They were interpreted as the remains of the medieval town and an oval-shaped village.